Unintentional paediatric falls from heights in France: epidemiology and prevention. (1st March 2011) - Rigou, A; Meyer, P; Girard, D; Jousset, N; Thelot, B
Abstract : Background: Unintentional paediatric falls from heights represent a longstanding public health problem, particularly in industrialised countries. Objective: To determine incidence rates and epidemiological risk factors of unintentional paediatric falls from heights in France. To help prevent these injuries. Method: An epidemiological survey was carried out in the Paris region (11.5 million inhabitants). It collected all unintentional falls from heights among children under 15 years of age (2.2 million) from 15 March to 15 October 2006. An organisation involved in epidemiological surveillance and prevention strategy was set up, including epidemiologists, medical doctors, sociologists and experts in regulation. Results: Sixty-four unintentional falls from heights were registered; 67% were children under 6 years of age, and 59% were male. In most of cases, young children fell due to lack of surveillance from adults. An item of furniture was located under the window or was moved to this area by the child in 42% of cases. Seven children (11%) died, and 11 children (17%) suffered from sequelae. A prevention campaign based on posters was initiated to alert parents on the risks of such injuries. Detailed recommendations concerning the evolution of equipments were published, and information on the risk and the severity of these injuries. A follow-up was set up under the auspice of the Ministry of Health. Conclusion: The epidemiological results led to issuing adapted prevention messages, and contributed to recommend regulation strategies, in order to decrease these injuries in France. In 2011 an epidemiological survey will contribute to assess the effectiveness of prevention.